Characterization of enzyme immobilization on novel supports—multi-walled carbon nanotube and alginate - Jameel, Ahmad Tariq; Mahmood, Labiba; Yusof, Faridah (Springer, Singapore, 2020)
Enzymes are preferred over chemical catalysts in a myriad of appli-cations owing to their high speciﬁcity, selectivity and moderate operating condi-tions. Enzymes in the soluble state are susceptible to instability and difﬁcult in separation. Immobilization of enzyme onto a support increases its physical and thermal stability, reusability and recovery from the reaction broth. Different support materials such as polymers, hydrogels, nanoparticles, nanoﬁbers and nano-scaffolds are being used for enzyme immobilization. Carbon-based nanomaterials have gained high popularity among different support materials. Here, we present the research ﬁndings on the immobilization of β-glucosidase onto two novel support materials, i.e., glutaraldehyde-activated multi-walled carbon nanotubes (MWCNTs) and Ca-alginate beads. The relative merits of the two supports are compared in terms of the performance of the enzyme in each case. β-Glucosidase immobi-lized on glutaraldehyde-modiﬁed MWCNTs exhibited higher residual activity and stability compared to the enzyme encapsulated in Ca-alginate beads. Kinetic study shows a higher enzyme afﬁnity for the substrate for enzyme immobilized onto MWCNT support compared to Ca-alginate. The overall results demonstrate that despite a general decrease in the enzyme activity due to immobilization, there is greater retention of activity of the immobilized enzyme upon multiple cycles of hydrolysis. This study provides distinct economic advantage of employing nanoparticles as support for enzyme immobilization for large-scale industrial applications.